An Overview on the Toxicological Properties of Ionic Liquids toward Microorganisms. Issue 4 (13th January 2020) - Sivapragasam, Magaret; Moniruzzaman, Muhammad; Goto, Masahiro
Abstract: Ionic liquids (ILs), a class of materials with unique physicochemical properties, have been used extensively in the fields of chemical engineering, biotechnology, material sciences, pharmaceutics, and many others. Because ILs are very polar by nature, they can migrate into the environment with the possibility of inclusion in the food chain and bioaccumulation in living organisms. However, the chemical natures of ILs are not quintessentially biocompatible. Therefore, the practical uses of ILs must be preceded by suitable toxicological assessments. Among different methods, the use of microorganisms to evaluate IL toxicity provides many advantages including short generation time, rapid growth, and environmental and industrial relevance. This article reviews the recent research progress on the toxicological properties of ILs toward microorganisms and highlights the computational prediction of various toxicity models. Abstract : Ionic liquids (ILs) have emerged as superior solvents for various biological applications. However, their use in industrial setting is constrained by their toxicity toward many microorganisms or their enzymes. Therefore, the practical uses of ILs must be preceded by suitable toxicological assessments. This article reviews the recent research progress on the toxicological properties of ILs toward microorganisms and their enzymes and highlights the computational prediction of various toxicity models.